2021
DOI: 10.46897/livestockstudies.610104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors Growth Traits of Akkaraman Sheep in Çankırı Province

Abstract: Small ruminants are important contributors of food supply chains throughout the world. In this study, characterization of distributions of birth weight, weaning weight, average daily gain and Kleiber ratio as well as estimation of effects of certain environmental factors on these traits were aimed in Akkaraman sheep raised around Çankırı province. For this purpose, the linear mixed model was fitted to estimate the effect of factors and to obtain the least square means for the traits. The effect of all studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…Various studies report that lamb birth weight is affected by the following factors: genetic factors (heterosis effect and breed) (Bancheva et al, 2022), non-genetic factors (production year (Kleemann et al, 1990;Mellado et al, 2016;Sudan et al, 2018;Sveinbjörnsson et al, 2021), lamb birth type (Sudan et al, 2018;Bancheva et al, 2022), weight and body condition of ewes (Kleemann et al 1990;Bancheva et al, 2022), lamb gender (Mellado et al, 2016;Sudan et al, 2018;Bancheva et al, 2022), litter size (Hinch et al, 1985;Kleemann et al, 1990;Mellado et al, 2016) weight of ewes at pairing (Hinch et al, 1985), inbreeding (Alsheikh, 2005), Ewes' feeding (Bancheva et al, 2022), herd (Baneh and Hafezian, 2009), season of lambing (Mellado et al, 2016). Similar to many studies in Akkaraman sheep, this study found that environmental factors such as ewe's age Noyan and Ceyhan, 2021;Aksoy et al, 2023), birth type (Aktaş and Doğan, 2014;Ceyhan et al, 2019;Sakar and Erişek, 2019;Noyan and Ceyhan, 2021;Sakar and Ünal, 2021;Aksoy et al, 2023;Tüfekci, 2023), and birth year (Ceyhan et al, 2019;Behrem, 2021;Noyan and Ceyhan, 2021;Aksoy et al, 2023;Tüfekci, 2023) significantly affected birth weight in Akkaraman lambs.…”
Section: Birth Weightsupporting
confidence: 86%
“…Various studies report that lamb birth weight is affected by the following factors: genetic factors (heterosis effect and breed) (Bancheva et al, 2022), non-genetic factors (production year (Kleemann et al, 1990;Mellado et al, 2016;Sudan et al, 2018;Sveinbjörnsson et al, 2021), lamb birth type (Sudan et al, 2018;Bancheva et al, 2022), weight and body condition of ewes (Kleemann et al 1990;Bancheva et al, 2022), lamb gender (Mellado et al, 2016;Sudan et al, 2018;Bancheva et al, 2022), litter size (Hinch et al, 1985;Kleemann et al, 1990;Mellado et al, 2016) weight of ewes at pairing (Hinch et al, 1985), inbreeding (Alsheikh, 2005), Ewes' feeding (Bancheva et al, 2022), herd (Baneh and Hafezian, 2009), season of lambing (Mellado et al, 2016). Similar to many studies in Akkaraman sheep, this study found that environmental factors such as ewe's age Noyan and Ceyhan, 2021;Aksoy et al, 2023), birth type (Aktaş and Doğan, 2014;Ceyhan et al, 2019;Sakar and Erişek, 2019;Noyan and Ceyhan, 2021;Sakar and Ünal, 2021;Aksoy et al, 2023;Tüfekci, 2023), and birth year (Ceyhan et al, 2019;Behrem, 2021;Noyan and Ceyhan, 2021;Aksoy et al, 2023;Tüfekci, 2023) significantly affected birth weight in Akkaraman lambs.…”
Section: Birth Weightsupporting
confidence: 86%
“…There are many studies examining the effects of different environmental factors on growth characteristics in various sheep breeds. Behrem (2021), in Akkraman sheep; Supakorn & Pralomkarn (2012), on the other hand, found the effect of birth type and gender on the weaning weights of Thai native, Anglo-Nubian, Boer, and Saanen goats as significant, and they determined that the weights of singleton and male lambs were higher. Moreover, Sánchez-Dávila et al (2015) the found lambing year had a significant effect on the weaning weight of Saint Croix hair sheep.…”
Section: Resultsmentioning
confidence: 99%
“…Akkaraman is a fat-tailed dual purpose (meat and milk) breed, and it is the most commonly raised indigenous sheep in Türkiye [ 5 , 6 ]. Populations of the breed have not been subjected to systematic genetic selection to increase fleece quality, leaving the wool characteristics relatively low, especially in terms of fineness, compared with fine-wool sheep such as the Merino.…”
Section: Introductionmentioning
confidence: 99%